Cytosine extensions optimize case activity for telomere length regulation: Implications for CRISPR-based therapies - A short communication - YRKM Sai (Annals of Molecular and Genetic Medicine - Peertechz Publications, 2021)
Telomeres are nucleoprotein structures that play a crucial role in maintaining genomic stability, and their length determines cellular lifespan. Telomere shortening is linked to cellular senescence and an increased risk of cancer. The CRISPR-Cas9 system has emerged as a tool for genome engineering and telomere length regulation. However, several factors, including chromatin accessibility, the efficiency of Double-Stranded Break (DSB) repair and the specificity of the sgRNA/Cas9 complex, limit the efficiency of Cas9-mediated telomere length regulation. Recent studies have demonstrated the use of modified Cas9 nucleases, such as Cas9-NG, and the development of modified sgRNAs to improve the efficiency of Cas9-mediated telomere length regulation. In this study, Bhattacharyya, et al. investigated the optimization of Cas9 activity through the addition of cytosine (C) extensions to the 5' end of sgRNAs. They found that C extensions significantly increased Cas9 activity at telomeres and demonstrated that the optimal length of C extensions was three Cs. The addition of C extensions did not affect the specificity of the sgRNA/Cas9 complex, as assessed by the frequency of off-target DSBs. These findings have important implications for the development of CRISPR-Cas9-based therapies for telomere-related diseases. Further studies are needed to confirm these findings and optimize the use of C extensions in different cell types and disease contexts.